Reductive weathering of black shale and release of barium during hydraulic fracturing. (February 2016) - Renock, Devon; Landis, Joshua D.; Sharma, Mukul
Abstract: Hydraulic fracturing is an important technological advance in the extraction of natural gas and petroleum from black shales, but water injected into shale formations in the fracturing process returns with extraordinarily high total-dissolved-solids (TDS) and high concentrations of barium, Ba. It is generally assumed that high TDS comes from the mixing of surface water (injected fluid) with Na–Ca–Cl formation brines containing elevated Ba, but the mechanisms by which such mixing might occur are disputed. Here we show that Ba in water co-produced with gas could originate from water-rock reactions, with Ba levels observed in produced waters reached on a time scale relevant to hydraulic fracturing operations. We examined samples from three drill cores from the Marcellus Shale in Pennsylvania and New York to determine the possible water-rock reactions that release barium during hydraulic fracturing. Two samples, one containing microcrystalline barite (BaSO4 ) and one without barite, contain elevated concentrations of Ba relative to the crustal average for shale rocks. A third sample is slightly depleted in Ba relative to the crustal average. Micro-XRF measurements and SEM/EDS analysis combined with chemical sequential extraction methods reveal that a majority of the Ba in all samples (55–77 wt.%) is present in clays and can only be leached from the rock by dissolution in hydrofluoric acid. Thus, a majority of barium in our samples is relatively inaccessible to leaching under hydraulic fracturing conditions. However, the balance of Ba in the rocks is contained in phases that are potentially leachable during hydraulic fracturing (e.g., soluble salts, exchangeable sites on clays, carbonates, barite, organics). We next studied how shale reacts with water at elevated temperatures (80 °C), low Eh (−100 to −200 mV), and a range of ionic strengths (IS = 0.85–6.4) that emulate conditions prevalent at depth during hydraulic fracturing. Our experimental results indicate that the amount of Ba released from the bulk rock has a positive correlation with the ionic strength of the reacting fluid. Between 5 and 25% of the total Ba in the rock can be leached from shale under ionic strength conditions and leachate compositions typical of produced waters over a contact time of just 7 days. We suggest that reductive weathering of black shale occurs during hydraulic fracturing due to: 1) Ba 2+ in clays exchanging with Na + and Ca 2+ ions that are present in high concentrations in produced water, and 2) increased solubility and dissolution kinetics of barite under high ionic strength conditions. At the low Eh conditions prevalent during hydraulic fracturing the sulfate deficient water allows Ba to be dissolved into the produced water. Based on Ba yields determined from laboratory leaching experiments of Marcellus Shale and a reasonable estimate of the water/rock mass ratio during hydraulic fracturing, we suggest that all of the Ba in produced water can be reconciled with leaching directly from the fractured rock. Highlights: 55–75% of the total Ba in Marcellus Shale is strongly partitioned into clays. 5–25% of the total Ba from the rock is released in high ionic strength solution. A water-to-rock ratio of the order of 10 −2 has been estimated.